A low carbohydrate diet affects autonomic modulation during heavy but not moderate exercise - Lima-Silva A.E. (2010)
The aim of this study was to examine the effects of low carbohydrate (CHO) availability on heart rate variability (HRV) responses during moderate and severe exercise intensities until exhaustion. Six healthy males (age, 26.5 ± 6.7 years; body mass, 78.4 ± 7.7 kg; body fat %, 11.3 ± 4.5%; 39.5 ± 6.6 mL kg-1 min-1) volunteered for this study. All tests were performed in the morning, after 8-12 h overnight fasting, at a moderate intensity corresponding to 50% of the difference between the first (LT1) and second (LT2) lactate breakpoints and at a severe intensity corresponding to 25% of the difference between the maximal power output and LT2. Forty-eight hours before each experimental session, the subjects performed a 90-min cycling exercise followed by 5-min rest periods and subsequent 1-min cycling bouts at 125% (with 1-min rest periods) until exhaustion, in order to deplete muscle glycogen. A diet providing 10% (CHOlow) or 65% (CHOcontrol) of energy as carbohydrates was consumed for the following 2 days until the experimental test. The Poicaré plots (standard deviations 1 and 2: SD1 and SD2, respectively) and spectral autoregressive model (low frequency LF, and high frequency HF) were applied to obtain HRV parameters. The CHO availability had no effect on the HRV parameters or ventilation during moderate-intensity exercise. However, the SD1 and SD2 parameters were significantly higher in CHOlow than in CHOcontrol, as taken at exhaustion during the severe-intensity exercise (P < 0.05). The HF and LF frequencies (ms2) were also significantly higher in CHOlow than in CHOcontrol (P < 0.05). In addition, ventilation measured at the 5 and 10-min was higher in CHOlow (62.5 ± 4.4 and 74.8 ± 6.5 L min-1, respectively, P < 0.05) than in CHOcontrol (70.0 ± 3.6 and 79.6 ± 5.1 L min-1, respectively; P < 0.05) during the severe-intensity exercise. These results suggest that the CHO availability alters the HRV parameters during severe-, but not moderate-, intensity exercise, and this was associated with an increase in ventilation volume. © 2009 Springer-Verlag.